A clinical profile of childhood alopecia areata in a tertiary care hospital in Chennai, India - Naveen Chandra Atluru; Vritika Gaddam; Sudha Rangarajan; Krishnakanth Muralidhar; Mahalakshmi Veeraraghavan (Wolters Kluwer Medknow Publications, 2019)
Background: Data of Clinical profile of childhood alopecia areata (AA) is inadequate in India. Hence this study was carried out. Materials and Methods: All new cases of childhood alopecia areata (AA) were studied from September of 2015 to September 2016, for a total duration of 1 year. In this prospective study, a total of 150 patients were diagnosed with AA, out of which 39 pediatric patients were enrolled in our study. Results: A total of 23 girls (58.97%) and 16 boys (40.02%) were seen with a ratio of 1.4:1 (female:male). All 39 patients are of South Indian decent and had an age of onset ranging from 2- to 18-year-old with the mean being 10.7 years. Twenty-four patients (61.5%) had a rapid onset of the disease, <6 months duration and only one patient had a previous episode of patchy hair loss. The majority of patients, 30 (76.9%), had a mild type of involvement, which was <25% of the scalp. A positive family history of AA was observed in 3 (7.7%) patients. A total of 17 (43.6%) patients had a history of atopy while only 7 (17.95%) patients had family members with a history of atopy. A positive family history of AA was seen in 3 (8.3%). Other systemic associations such as vitiligo, lichen planus, and Down's syndrome were rare. Conclusions: The age of onset, a positive family history of AA, and associated autoimmune diseases or atopic disorders were observed to not have any influence on the severity of the disease. The results were compared with those reported elsewhere for the similar age group.